Influence of size reduction treatments on sugar recovery from Norway spruce for butanol production. (June 2018) - Yang, Ming; Xu, Minyuan; Nan, Yufei; Kuittinen, Suvi; Kamrul Hassan, Md.; Vepsäläinen, Jouko; Xin, Donglin; Zhang, Junhua; Pappinen, Ari
Highlights: Effect of size reduction treatments on sugar recovery of Norway spruce was studied. Sugar recoveries from chipped and mashed spruce were higher than from milled spruce. HPAC pretreatment resulted in higher sugar recoveries than DA pretreatment. The sugar recoveries were not correlated with fiber length of pretreated materials. Norway spruce chipped to a 20 mm length is applicable for butanol fermentation. Abstract: This study investigated whether the effectiveness of pretreatment is limited by a size reduction of Norway spruce wood in biobutanol production. The spruce was milled, chipped, and mashed for hydrogen peroxide-acetic acid (HPAC) and dilute acid (DA) pretreatment. Sugar recoveries from chipped and mashed spruce after enzymatic hydrolysis were higher than from milled spruce, and the recoveries were not correlated with the spruce fiber length. HPAC pretreatment resulted in almost 100% glucose and 88% total reducing sugars recoveries from chipped spruce, which were apparently higher than DA pretreatment, demonstrating greater effectiveness of HPAC pretreatment on sugar production. The butanol and ABE yield from chipped spruce were 126.5 and 201.2 g/kg pretreated spruce, respectively. The yields decreased with decreasing particle size due to biomass loss in the pretreatment. The results suggested that Norway spruce chipped to a 20 mm length is applicable to the production of platform sugars for butanol fermentation.